Small Bowel Review: Part I - ABR Thomson; JA Thomson; MJ Ropeleski; GE Wild (Canadian Journal of Gastroenterology)
Major scientific advances have been made over the past few years in the areas of small bowel physiology, pathology, microbiology and clinical sciences. Over 1000 papers have been reviewed and a selective number are considered here. Wherever possible, the clinical relevance of these advances have been identified. There have been a number of important and/or interesting developments in the past year that have clinical significance.